2010
DOI: 10.1016/j.cortex.2009.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for topographic organization in the cerebellum of motor control versus cognitive and affective processing

Abstract: Patients with cerebellar damage often present with the cerebellar motor syndrome of dysmetria, dysarthria and ataxia, yet cerebellar lesions can also result in the cerebellar cognitive affective syndrome, including executive, visual-spatial, and linguistic impairments, and affective dysregulation. We have hypothesized that there is topographic organization in the human cerebellum such that the anterior lobe and lobule VIII contain the representation of the sensorimotor cerebellum; lobules VI and VII of the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

72
895
5
15

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,173 publications
(987 citation statements)
references
References 224 publications
(264 reference statements)
72
895
5
15
Order By: Relevance
“…The cerebellar hemispheres have been implicated in higher cognitive processes (Kelly & Strick, 2003; Stoodley & Schmahmann, 2009; Stoodley & Schmahmann, 2010; Stoodley et al, 2012) and thus, the foliation defects identified in the anterior cerebellum tentatively suggest a connection between these cerebellar defects and intellectual disability and autistic phenotypes associated with CHARGE syndrome. Separately, the relationship between cerebellar anomalies and autism is well established and in contrast to other brain regions, gross and microscopic changes in the cerebellum are most frequently associated with autism (Becker & Stoodley, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The cerebellar hemispheres have been implicated in higher cognitive processes (Kelly & Strick, 2003; Stoodley & Schmahmann, 2009; Stoodley & Schmahmann, 2010; Stoodley et al, 2012) and thus, the foliation defects identified in the anterior cerebellum tentatively suggest a connection between these cerebellar defects and intellectual disability and autistic phenotypes associated with CHARGE syndrome. Separately, the relationship between cerebellar anomalies and autism is well established and in contrast to other brain regions, gross and microscopic changes in the cerebellum are most frequently associated with autism (Becker & Stoodley, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…MCP mot is predominantly associated with motor‐sensory function, originates in the caudal pons and runs superior‐medially toward the anterior cerebellum. Past studies have found evidence of a rostral pons to posterior cerebellum and caudal pons to anterior cerebellum connection (Schmahmann, Rosene, & Pandya, 2004; Spitzer & Karplus, 1907; Sunderland, 1940; Von Bechterew, 1885), which is further supported by evidence that points to a caudal pons anterior lobe of cerebellum sensorimotor representation (Buckner, Krienen, Castellanos, Diaz, & Yeo, 2011; Schmahmann, MacMore, & Vangel, 2009; Schmahmann & Pandya, 1997; Schmahmann & Sherman, 1998; Stoodley & Schmahmann, 2010). The superior cerebellar peduncle pathway (SCP) consists primarily of efferent output neurons traveling from the cerebellum to higher brain centers via the mid‐brain (HĂŒttlova et al., 2014; Mittal et al., 2014; Ojemann et al., 2013; Schmahmann et al., 2004; Takahashi, Song, Folkerth, Grant, & Schmahmann, 2013; Von Bechterew, 1885; Wang et al., 2003).…”
Section: Introductionmentioning
confidence: 89%
“…Although the cerebellum has been traditionally associated with motor control, recently a growing body of clinical and experimental evidences has suggested that it may be also involved in non-motor functions [6][7][8]. In fact, it has been shown that cerebellar abnormalities, e.g.…”
Section: Introductionmentioning
confidence: 99%